INCREASING OF WEAR RESISTANT OF HIGH-MANGANESE STEEL - M. S. Shramko; V. P. Karginov; A. V. Maljj; A. D. Leshchenko; V. I. Minakova; V. N. Jashchenko (Литьë и металлургия)
The aim of the present work is development of highmanganese steel, which could provide high level of mechanical characteristics and wear resistance of details of mining and mining-processing equipment operating in terms of abrasive wear with slight impact loads.